Assessing the effects of design modifications on the use of wildlife exits designed for endangered Texas ocelots - Rupesh Maharjan; Jamie E. Langbein; John H. Young; Kevin Ryer; Alejandro Fierro-Cabo; Md Saydur Rahman; Richard J. Kline (PLoS ONE, 2025)
Roadside exclusionary fencing is commonly used on highways to prevent wildlife-vehicle collisions. Although it can mitigate wildlife road mortality by limiting their access to the road, it can also create a barrier for wildlife stranded within the right-of-way. On State Highway 100 in Texas, the Texas Department of Transportation installed 10 wildlife exits (WEs) to allow endangered ocelots and other wildlife to escape the fenced roadway and minimize wildlife-vehicle collisions. Our study compared three types of WE designs within the same area from 2019 to 2024 to assess their effectiveness. The first design (Design A) was without a door and berm, and the second design (Design B) had a raised berm (10 WE sites) with a door (six WE sites) and no door (four WE sites). Lastly, a third design (Design C) had all the structural features of Design B, except for the raised berm removed from all ten WE sites. We used the approaches of four meso-carnivore target species (coyote, bobcat, northern raccoon, and striped skunk) as a metric and binomial generalized linear model as a statistical method to evaluate the effectiveness between three designs. The statistical analysis showed that the raised berm in Design B was the major cause for a decline in the approaches of meso-carnivore communities toward the WE sites. With the berm removal in Design C, the approaches of target species from road to habitat increased significantly in the sites without a door. Our study indicates that the WE door design might be another structural cause for limiting its effectiveness, where significantly lower approaches were recorded for meso-carnivores in the sites with a door compared to those without a door in Design C.